The Relationship Between Physical Activity and Quality of Life in Chronic Kidney Failure Patients Undergoing Hemodialysis - Zulfiana Nurlaili; Fahrun Nur Rosyid; Puji Kristini (GLOBAL HEALTH SCIENCE GROUP, 2024)
Patients undergoing hemodialysis often report lower quality of life. Many factors cause this decline, and physical exercise is one of them. Doing physical activity helps patients live a better life. This study aimed to analyze the relationship between physical activity and the quality of life of CKD patients undergoing hemodialysis at Pandan Arang Hospital, Boyolali. This research method uses a descriptive correlative design with a cross-sectional approach. The sample of this study consisted of 121 respondents selected using accidental random sampling techniques. Data were collected using the WHOQOL-BREF questionnaire to measure quality of life and IPAQ to measure physical activity, and bivariate test data analysis was performed using the Spearman statistical test. With a significance of alpha = 0.05. The results showed that most patients had high levels of physical activity (69.4%) and high quality of life (66.1%). Physical activity and quality of life were significantly correlated (p-value <0.001), meaning patients' quality of life improved with increased physical activity. A good correlation exists between the quality of life and the physical activity level of hemodialysis patients with chronic kidney disease. Therefore, therapy that emphasizes enhancing the patient's physical activity is strongly advised as part of comprehensive care to improve the quality of life for patients receiving hemodialysis. Health workers should support rehabilitation and physical education programs to achieve the best results.